BMT Performance Assessment Analysis Based on the Maqoshid Syariah Index (Case Study of BMT in South Tangerang City) - Hadi, Syamsul; Koesmawan, Koesmawan (Budapest International Research and Critics University, 2023)
The development of Baitul Mal wat Tamwil (BMT) in Indonesia is increasingly showing a significant progress trend with the main target being micro business actors who are generally located in rural and urban areas. Baitul Mal wat Tamwil (BMT) as an institution that upholds sharia principles has not yet found an assessment format based on sharia principles. The Maqashid Sharia index as an alternative solution for measuring performance has 3 achievement indicators, namely: Education (Individual Education), Upholding Justice (Establishing Justice) and Public Welfare (Public Interest). The aim of this research is to analyze and provide an assessment of Baitul's performance. Mal Wat Tamwil (BMT) in the South Tangerang city area using the Maqoshid Syariah Index method. This research is quantitative descriptive. Data obtained from financial reports for 2018-2020 as well as interviews with managers or daily administrators of Baitul Mal wat Tamwil (BMT). Performance measurement is carried out by determining ratio values based on financial reports as an achievement of the Maqoshid Syariah Index perspective. The results of the research show that BMT UBASYADA has the highest rating value according to the Maqoshid Syariah Index with a total value of1.49973485followed by BMT Al-Fath with value1.28249458, BMT At-Taqwa with value1.015181493next there is BMT Mujahidin with value0.85997638as well as BMT UMJ with grades0.59056637. Overall, the conclusion of this research shows that Baitul Mal wat Tamwil (BMT), which is the object of research, has implemented sharia principles well, so in the future it needs to be used as motivation for Baitul Mal wat Tamwil (BMT) to continue to improve its performance in accordance with sharia principles.